Effect of Online Claims on The Participant Satisfaction Level BPJS Employment Meulaboh Branch - Sri Putri Ayuni Mulia; Cut Devi Maulidasari (International Journal of Social Service and Research, 2021)
This study was conducted to determine the effect of online claims on the satisfaction level of BPJS Employment participants in the Meulaboh Branch. The method used in this study is a quantitative research method. This research uses primary data by distributing questionnaires and secondary data obtained from research method books, journals, participant documents and related literature. the distribution of questionnaires was carried out online to participants of BPJS Employment Meulaboh Branch, the population in this study were participants of BPJS Ketenagakerjaann Meulaboh Branch who made claims online, the number of respondents who were sampled in the study were 41 respondents. Data analysis was carried out using Validity test, Reliability test, Simple Linear Regression test and Hypothesis test using t test. Based on the results of research on the Effect of Online Claims on the Satisfaction Level of BPJS Employment Participants in the Meulaboh Branch, the results of a simple regression analysis with the help of SPSS version 20.0 are known to have R square of 0.710, the figure shows that the influence of the Online Claims variable (X) on the Satisfaction Level (Y) is 71 % while the remaining 29% is influenced by other factors. The results of the calculation of the hypothesis using the t-test technique with the help of SPSS version 20.0, it is known that the significant value of the Online Claims variable is 0.000 <0.5 and the t-count value > t table (2.02439) which is 9.777, it can be concluded that there is a significant influence between online claims on satisfaction level of BPJS Employment participants in Meulaboh Branch.